La reconnaissance comme puissance spéculative du pacte social. Reflexión sur la lecture hégélienne de Hobbes - Vigneault, Luc (Revista de Filosofía, 2006)
Contemporary debates about political identity are deeply grounded in Hegelian’s paradigm of State. Hegel develops an original identity structure, build on a dynamics of recognition which allows interaction between subjective and objective liberty. The purpose of this Hegelian approach is to define a State which would be able to auto-justify and legitimize itself. This article studies the Hegelian theory of recognition, as a critical reading of Hobbes and of the philosophical insufficiency of the contractualist theories. Analyzing the concept of recognition may lead us to a better understanding of multiculturalism and political pluralism, as key concepts in today’s society.
Keywords: State’s Theorie; Social Contract; Hobbes; Hegel; Recognition; Citizenship